2016
DOI: 10.3390/molecules21050579
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of Antiproliferative Activity of New Benzimidazolehydrazones

Abstract: Abstract:The synthesis and antiproliferative activity of new benzimidazole derivatives bearing an hydrazone mojety at the 2-position is described. The new N 1 -(4-arylidene)-1H-benzo[d]imidazole-2-carbohydrazides were evaluated for their cytostatic activity toward the murine leukemia (L1210), human T-cell leukemia (CEM), human cervix carcinoma (HeLa) and human pancreas carcinoma cells (Mia Paca-2). A preliminary structure-activity relationship could be defined. Some of the compounds possess encouraging and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…This is evident from the results of CCD-16-Co cells that tolerated approximately 5000 nM MLT-401. Similar effects were observed with other arylidene derivatives studied using various cancer models [9, 27]. The selective inhibition of cancerous cells over normal cells both in normoxic and marginal hypoxic conditions shows that the molecule works downstream of the hypoxic conditions.…”
Section: Discussionsupporting
confidence: 65%
“…This is evident from the results of CCD-16-Co cells that tolerated approximately 5000 nM MLT-401. Similar effects were observed with other arylidene derivatives studied using various cancer models [9, 27]. The selective inhibition of cancerous cells over normal cells both in normoxic and marginal hypoxic conditions shows that the molecule works downstream of the hypoxic conditions.…”
Section: Discussionsupporting
confidence: 65%
“…The structures of the novel compounds were confirmed by using IR, 1 H NMR, 13 C NMR spectra, and mass analysis. Spectral (IR, 1 H NMR, 13 C NMR) data of the synthesized compounds (2a-k) were consistent with the literature [32][33][34]. The IR spectra of the products are characterized by the presence of absorption bands at 2936-2730 and 1588-1441 cm À1 corresponding to the aliphatic C-H, C --C, and C --N functions in the structure.…”
Section: Resultsmentioning
confidence: 96%
“…In conclusion, we synthesized 2-substitutedbenzyl-4(7)-phenyl-1H-benzo[d]imidazole derivatives (2a-k) and characterized by using IR, 1 H NMR, 13 C NMR spectra, and mass analysis. Tyrosinase inhibitory effects and antioxidant activities of the synthesized benzimidazole derivative compounds were evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed the importance of benzimidazoles as anticancer agents including bendamustine, dovitinib, Hoechst 33342, and Hoechst 33258 (Fig. 1) [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%